Ventilação não invasiva com pressão positiva para insuficiência respiratória aguda após cirurgia abdominal alta: revisão sistemática - Faria, Débora De Almeida Silva [UNIFESP] (2019)
Objectives: To assess the effectiveness and safety of noninvasive positive pressure ventilation (NPPV), that is, continuous positive airway pressure (CPAP) or bilevel NPPV, in reducing mortality and the rate of tracheal intubation in adults with acute respiratory failure after upper abdominal surgery, compared to standard therapy (oxygen therapy), and to assess changes in arterial blood gas levels, hospital and intensive care unit (ICU) length of stay, gastric insufflation, and anastomotic leakage. Search methods: We searched the following databases: the Cochrane Handbook for Systematic Reviews of Interventions CENTRAL, MEDLINE, EMBASE, PEDro, CINAHL, EBSCOhost, and LILACS. We reviewed reference lists of included studies and contacted experts. We checked databases of ongoing trials such as www.controlledtrials.com and www.trialscentral.org. We did not apply language restrictions. The date of the search was May 2015. We selected randomized or quasi-randomized controlled trials involving adults with acute respiratory failure after upper abdominal surgery who were treated with CPAP or bilevel NPPV with, or without, drug therapy as standard medical care, compared to adults treated with oxygen therapy with, or without, standard medical care. The selection of studies, judgment of risk of bias and data extraction was performed independently by two review authors. Main results: We included two trials involving 269 participants. We judged both trials at high risk of bias. Compared to oxygen therapy, CPAP or bilevel NPPV may reduce the rate of tracheal intubation (risk ratio (RR) 0.25; 95% confidence interval (CI) 0.08 to 0.83; low quality evidence) with a number needed to treat for an additional beneficial outcome of 11. There was very low quality evidence that the intervention may also reduce ICU length of stay (mean difference (MD) -1.84 days; 95% CI -3.53 to -0.15). We found no differences for mortality (low quality evidence) and hospital length of stay. There was insufficient evidence to be certain that CPAP or NPPV had an effect on anastomotic leakage, pneumonia-related complications, and sepsis or infections. Findings from one trial of 60 participants suggested that bilevel NPPV, compared to oxygen therapy, may improve blood gas levels and blood pH one hour after the intervention (partial pressure of arterial oxygen (PaO2): MD 22.5 mm Hg; 95% CI 17.19 to 27.81; pH: MD 0.06; 95% CI 0.01 to 0.11; partial pressure of arterial carbon dioxide (PCO2) levels (MD -9.8mmHg; 95% CI -14.07 to -5.53). The trials included in this systematic review did not present data on the following outcomes that we intended to assess: gastric insufflation, fistulae, pneumothorax, bleeding, skin breakdown, eyeirritation, sinus congestion, oronasal drying, and patient-ventilator asynchrony. Authors’ conclusions: The findings of this review indicate that NPPV is an effective and safe intervention for the treatment of adults with acute respiratory failure after upper abdominal surgery. Its use is recommended in order to reduce the need for intubation (considering the size of the effect observed through the NNT), however, the quality of the evidence is low which suggests the need for studies with better control of bias.